Landasan Religius dan Etis dalam Pengambilan Keputusan Investasi: Tinjauan Sistematis dari Perspektif Islam dan Global - Mohammad Ilham Najmuddin; Negina Kencono Putri (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to review the literature on ethics and religiosity in investment decision-making from Islamic and global perspectives. The study uses a Systematic Literature Review (SLR) method by analyzing 20 scientific articles published between 2020 and 2025. The findings identify key themes related to Sharia-based investment, Environmental, Social, and Governance (ESG), and Socially Responsible Investment (SRI). The results show that ethics and religiosity influence investors’ preferences and behavior in making investment decisions. Globally, ESG and SRI encourage investors to consider environmental sustainability, social responsibility, and corporate governance alongside financial returns. From an Islamic perspective, investment decisions are guided by Sharia principles emphasizing halal practices, justice, and the avoidance of riba, gharar, and maisir. However, both approaches face challenges, including inconsistent ethical implementation, limited assessment standards, low investor understanding, and profit-oriented decisions under market pressure. The study also reveals that religiosity does not always directly determine investment decisions, as it is influenced by financial literacy, ethical understanding, and social and psychological factors. Therefore, strengthening ethics-based financial literacy and consistent regulations is recommended to support effective ethical investment practices.